2015
DOI: 10.1080/07315724.2014.896230
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Components of Mother Vinegar

Abstract: It was concluded that mother of vinegar produced by natural acetic acid bacteria contains significant bioactive substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The changes in antiradical activity depending on dilution of samples were similar to the results of the study conducted by Aydin and Gokisik (5). Many studies indicated that the antioxidant capacity of vinegar was highly correlated with their phenolic contents being affected by the raw materials and manufacturing processes (6,47). Similarly, a correlation was found between phenolic content and antiradical activity in this study.…”
Section: Discussionsupporting
confidence: 84%
“…The changes in antiradical activity depending on dilution of samples were similar to the results of the study conducted by Aydin and Gokisik (5). Many studies indicated that the antioxidant capacity of vinegar was highly correlated with their phenolic contents being affected by the raw materials and manufacturing processes (6,47). Similarly, a correlation was found between phenolic content and antiradical activity in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Phenolic compounds in apple juice samples were determined according to the method of Kelen et al (2004) with modifications reported by Aykin et al (2014).…”
Section: Determination Of Phenolics By Hplcmentioning
confidence: 99%
“…In contrast, grain vinegars contain only a small amount of gallic acid, catechins, and other phenolic compounds, which are high in fruit vinegars (Garcı́a Parrilla and others ; Andlauer and others ; Plessi and others ; Jeong and others ; Budak and Guzel‐Seydim ; Cerezo and others ). Apple vinegars contain large amounts of chlorogenic acid, which is present in the raw material (Andlauer and others ; Nakamura and others ; Li and others ; Aykın and others ). In addition, the fermentation process also affects the types and contents of polyphenols.…”
Section: The Sources Of Functional Ingredients In Vinegarsmentioning
confidence: 99%